The impact of the COVID-19 pandemic on global energy consumption: a systematic review - Mohammad Hadi Dehghani; Nabi Shariatifar; Parisa Sadighara; Mina Aghaei; Reza Zeraatkar (International Archives of Health Sciences, 2024)
Objectives: The COVID-19 pandemic has had a profound impact on human social and economic structures, making it one of the most significant crises of the 21st century. The production and consumption of energy sources, such as electricity, oil, and gas, have also been affected by the pandemic. Therefore, this study aims to systematically review the effects of the COVID-19 pandemic on energy consumption.Methods: This study presents a systematic review of the impact of the coronavirus on energy consumption. Initially, relevant keywords were selected, and a systematic search of studies was conducted in databases including Web of Science, PubMed, Scopus, and ScienceDirect from 2020 to May 2022. Following screening, articles meeting the eligibility criteria were included in the study.Results: Through this systematic review, a total of 19,551 studies were identified, of which 18 met the eligibility criteria. All included studies investigated electricity consumption, while two studies focused on gas and fuel consumption, and only one study examined heating oil consumption. The most significant decreases in electricity, natural gas, and transportation fuel consumption were 55.4%, 32.4%, and 75.9%, respectively. On the other hand, heating oil consumption saw an increase of 12%.Conclusion: The results of this systematic review indicate that the COVID-19 pandemic has resulted in reduced energy consumption across various sectors, including electricity, transportation fuel, and natural gas, leading to a decrease in greenhouse gas emissions. However, some studies reported an increase in electricity consumption in the residential sector due to prolonged periods of staying at home and remote work during quarantine.